Peran Event and Experiences dalam Membangun Loyalitas Merek JKT48 pada Penggemar di Denpasar - I Putu Andrean Guritna Putra; Sahri Aflah Ramadiansyah (Badan Penerbit STIEPARI Press, 2026)
This study aims to analyze the role of Events and Experiences in building JKT48 brand loyalty among fans residing in Denpasar. Integrated Marketing Communication (IMC) marketing communication strategies, particularly those focused on events and live experiences, are the primary focus in consistently conveying brand messages and building emotional connections between JKT48 and its fans. Activities such as Mini Live Performances and Meet and Greets serve not only as promotional tools but also as memorable experiences that foster brand engagement and a sense of belonging. This study uses a descriptive qualitative approach by exploring the experiences of fans who actively participate in various JKT48 activities in Denpasar. The results show that direct event participation has a significant impact on the formation of fan loyalty, both emotionally and behaviorally. Positive experiences created through direct interactions strengthen the bond between fans and JKT48. These findings contribute to JKT48 management and the entertainment industry in designing experience-based communication strategies to increase brand loyalty and build sustainable long-term relationships with fans.